Relations between virtues and positive mental health in a Korean population: A Multiple Indicators Multiple Causes (MIMIC) model approach. (5th August 2014) - Lim, Young‐Jin
<x xml:space="preserve">Abstract</x> A Multiple Indicators Multiple Causes (MIMIC) approach was applied to investigate the relationship between virtues and positive mental health as determined using the Character Strength Test and the Mental Health Continuum‐Short Form. The study participants were 876 college students (54% women; overall mean age [SD] 21.50 years [2.35]) recruited from introductory psychology courses at two universities in Seoul. Findings revealed that the intellectual virtues of college students predicted subjective well‐being according to all emotional, social and psychological measures. Results are discussed in the context of previous work using the Values in Action classification of virtues and character strengths. In addition, implications regarding understanding the nature and possible origins of positive mental health are outlined.